Sleeping on the job : energypods at HuffPost - MacDougall, Alexandra E., (SAGE Business. Cases., 2022)
Arianna Huffington, founder of the Internet news site HuffPost, collapsed from exhaustion in 2007. Ever since, she has made sleep a priority, and has worked to normalize workplace napping for all by introducing designated napping spaces at HuffPost. These napping spaces are outfitted with devices known as the EnergyPod, which are specifically designed to provide employees with a private, relaxing space for napping at work. This case provides an opportunity for students to contemplate the nature of today's workplace and the extent to which napping should play a role in it. Following discussion of the overall benefits and risks presented by napping on the job, this case asks students to generate recommendations for organizations that are considering implementing napping at work policies.